The Grid Voltage's Asymmetrical Fault Detection Method based on Variable-Step LMS Adaptive Notch Filter Algorithm. Issue 4 (May 2019) - Wang, Yifan; Wang, Shuhong; Zhang, Ailing; Wang, Jingxuan
Abstract: For wind turbine systems (WTS), the grid voltage fault detection algorithm determines the response speed of WTS to grid voltage fault. This paper proposed a sort of voltage asymmetrical fault detection method, to detect negative-sequence component in grid voltage, variable-step (VS) least mean square (LMS) adaptive notch filter (ANF) is applied to eliminate the 2nd-harmonic frequency component. The application of ANF can separate negative-sequence component from grid voltage, therefore the voltage asymmetrical fault can be detected; the self-tuning of controllable parameters of ANF can be realized by the LMS adaptive algorithm, which is convenient and efficient in practical application; furthermore, because the variable step size adjustment is adopted, the contradiction between convergence rate and steady-state error of ANF can be solved. The MATLAB/Simulink simulation and FFT analysis results are in conformity with the theorical analysis, which proves the feasibility of the method.